Anemia and Iron-Deficiency Anemia in Children Born to Mothers with HIV in Western Kenya - Eren Oyungu; Anna W. Roose; Ananda R. Ombitsa; Ziyi Yang; Rachel C. Vreeman; Megan S. McHenry (SAGE Publishing, 2021)
The objective of this study was to determine and compare anemia and iron-deficiency anemia (IDA) rates in young Kenyan children who are HIV infected (HI), HIV exposed, uninfected (HEU), and HIV unexposed (HU). Questionnaires, anthropometrics, and blood samples were collected from HI, HEU, and HU aged 18 to 36 months. Descriptive statistics, Fisher's exact tests, and linear regression were used for analysis. Of 137 total participants, HI (n = 18), HEU (n = 70), and HU (n = 49), 61.1%, 53.6%, and 36.7%, respectively, were anemic, with mean hemoglobin levels highest in HU ( P  = .006). After adjusting for covariates, HI (β = −9.6, 95% CI:−17.3 to −2.0) and HEU (β = −7.4, 95% CI: −12.9 to −1.9) had lower hemoglobin levels compared with HU. The proportion of children with IDA did not differ significantly across groups ( P  = .08). HEU have rates of anemia and IDA similar to HI. Anemia risk is generally higher in HEU than HU, even after adjusting for covariates.